PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INDONESIA BERBASIS CHATGPT FOKUS KETERAMPILAN MENULIS KELAS V SD NEGERI DI DABIN 1 KECAMATAN AMPELGADING - Pitta Danuwindah Nareswari; Rahmad Agung N; Basukiyatno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Developing students' communication skills in Indonesian language learning, particularly in writing, plays a fundamental role. However, mastering specific genres of writing, such as summarizing or creating expository texts, often poses a significant challenge at the elementary school level. Conventional teaching approaches are frequently unable to arouse student interest and facilitate deep understanding, which leads to low motivation and suboptimal learning outcomes. In response to these problems, this study aims to design an Indonesian language learning module based on ChatGPT, focusing on writing skills for fifth-grade students at SD Negeri in Dabin 1, Ampelgading District. This research uses the Research and Development (R&D) method with the 4D model, limited to the "Develop" stage. Data collection was conducted through interviews, observations, documentation, and expert validation. The research results show that the designed module was declared "very valid" by material and media experts. Furthermore, a limited trial proved that this module successfully increased students' interest and enthusiasm for writing and received positive feedback from teachers regarding its practicality. The utilization of ChatGPT allows for more engaging, responsive, and contextual learning interactions, while also affirming its potential as an innovative alternative in Indonesian language instruction.